1973
DOI: 10.1128/jb.114.3.974-979.1973
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible Plasmid Coding Early Enzymes of Naphthalene Oxidation in Pseudomonas putida

Abstract: The capacity of Pseudomonas putida PpG7 (ATCC 17,485) to grow on naphthalene, phenotype Nah+, is lost spontaneously, and the frequency is increased by treatment with mitomycin C. The Nah+ growth character can be transferred to cured or heterologous fluorescent pseudomonads lacking this capacity by conjugation, or between phage pfl6-sensitive strains by transduction. After mutagenesis, strains can be selected with increased donor capacity in conjugation. Clones which use naphthalene grow on salicylate and carry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(90 citation statements)
references
References 19 publications
(35 reference statements)
2
88
0
Order By: Relevance
“…Virtually all that is known of the biochemistry and genetics of bacterial naphthalene metabolism was gained from analysis of pseudomonads such as Pseudomonas putida G7 and its resident plasmid, NAH7 [1,2]. Studies on naphthalene metabolism by pseudomonads were instrumental in developing an understanding of aromatic hydrocarbon metabolism and evolutionary relationships between diverse biodegradative strains.…”
Section: Introductionmentioning
confidence: 99%
“…Virtually all that is known of the biochemistry and genetics of bacterial naphthalene metabolism was gained from analysis of pseudomonads such as Pseudomonas putida G7 and its resident plasmid, NAH7 [1,2]. Studies on naphthalene metabolism by pseudomonads were instrumental in developing an understanding of aromatic hydrocarbon metabolism and evolutionary relationships between diverse biodegradative strains.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmids NAH and pBS3 controlling degradation of naphthalene via the meta-pathway of catechol oxidation were used [1,2]. Plasmid pBS4 codes for the oxidation of naphthalene via gentisic acid [3].…”
Section: Methodsmentioning
confidence: 99%
“…Studies of naphthalene degradative plasmids [1][2][3][4][5] showed them to control various biochemical pathways of naphthalene oxidation (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the naphthalene and salicylate utilizing phenotypes in P. putida G7 have been attributed to the NAH catabolic plasmid [5]. It was shown that the naphthalene catabolic genes are organized into two nah operons: the ¢rst operon encoding the conversion of naphthalene to salicylate (upper pathway), which includes genes nahABCDEF, and the second operon (nahGHIJK) encoding the oxidation of salicylate [6].…”
Section: Introductionmentioning
confidence: 99%